Management of acute coronary syndromes during the COVID-19 outbreak in Lombardy: The "macro-hub" experience. (December 2020) - Carugo, Stefano; Ferlini, Marco; Castini, Diego; Andreassi, Aida; Guagliumi, Giulio; Metra, Marco; Lombardi, Carlo; Cuccia, Claudio; Savonitto, Stefano; Piatti, Luigi; D'Urbano, Maurizio; Lettieri, Corrado; et al.
Abstract: Background: During the COVID-19 outbreak, healthcare Authorities of Lombardy modified the regional network concerning time-dependent emergencies. Specifically, 13 Macro-Hubs were identified to deliver timely optimal care to patients with acute coronary syndromes (ACS). Aim of this paper is to present the results of this experience. Methods and Results: This is a multicenter, observational study. A total of 953 patients were included, presenting with STEMI in 57.7% of the cases. About 98% of patients received coronary angiography with a median since first medical contact to angiography of 79 (IQR 45–124) minutes for STEMI and 1262 (IQR 643–2481) minutes for NSTEMI. A total of 107 patients (11.2%) had SARS-CoV2 infection, mostly with STEMI (74.8%). The time interval from first medical contact to cath-lab was significant shorter in patients with COVID-19, both in the overall population and in STEMI patients (87 (IQR 41–310) versus 160 (IQR 67–1220) minutes, P = 0.001, and 61 (IQR 23–98) versus 80 (IQR 47–126) minutes, P = 0.01, respectively). In-hospital mortality and cardiogenic shock rates were higher among patients with COVID-19 compared to patients without (32% vs 6%, P < 0.0001, and 16.8% vs 6.7%, P < 0.0003, respectively). Conclusions: During the COVID-19 outbreak in Lombardy, the redefinition of ACS network according to enlarged Macro-Hubs allowed to continue with timely ACS management, while reserving a high number of intensive care beds for the pandemic. Patients with ACS and COVID-19 presented a worst outcome, particularly in case of STEMI.